(untitled) ("Journal "U". Economy. Management. Finance.", 2024)
The article examines current trends and innovative approaches to financial instruments that are used in modern business, analyzes the prospects for the use of innovative financial instruments such as blockchain technologies, digital currencies, crowdfunding, and others. Special attention is paid to the risks associated with the use of such tools and ways to minimize them. The authors of the article offer practical recommendations on effective risk management when using innovative financial instruments. This article will be useful for specialists in the field of finance, risk management, as well as for entrepreneurs and investors interested in using innovative approaches to financing and investing.